DEVELOPMENT OF INTERACTIVE GAME-BASED EDUCATIONAL SYSTEMS FOR STUDENTS USING SUPERCOMPUTER MODELING - Khudayberganov Yashin; Khonturayev Ibrokhim (Journals Park Publishing, 2025)
This article discusses the development of interactive educational systems based on supercomputer modeling and their impact on students’ learning processes. The high computational power of supercomputers allows for the simulation of complex processes, enabling students to study real-life scenarios in a virtual environment. Interactive games increase students’ interest in lessons and ensure their active participation. The article outlines the stages of developing such systems, the technologies and algorithms used, and presents examples from both Uzbekistan and international practices. In conclusion, it is emphasized that the integration of supercomputer-based modeling and interactive game-based educational systems contributes to making the learning process more effective and engaging.
Keywords: Supercomputer, modeling, interactive game, educational technologies, artificial intelligence, AR/VR, individualized approach.